Rapid Point-Of-Care Serology and Clinical History Assessment Increase Protection Provided by RT-PCR Screening: A Pilot Study Involving Three Nursing Homes in Brescia, a Hotspot of Lombardy - Savio, Antonella; Calza, Stefano; Guerrini, Gianbattista; Romano, Valentina; Marchina, Eleonora (Frontiers in Public Health, 2021)
COVID-19 outbursts have been registered worldwide within care homes with asymptomatic transmission combined with shortage/inaccuracy of diagnostic tests undermining the efforts at containment of the disease. Nursing facilities Lombardy (Italy) were left with no, or limited, access to testing for eight weeks after the outbreak of COVID-19. This study includes 246 residents and 286 workers of three different nursing homes in Brescia-Lombardy. Clinical questionnaires and rapid serology tests were devised to integrate the data of the first available RT-PCR screening. Follow-up serology after 60-days was performed on 67 of 86 workers with positive serology or clinically suspicious. 37 residents and 18 workers had previous positive RT-PCR. Thorough screening disclosed two additional RT-PCR-positive workers. Serology screening revealed antibodies in 59 residents and 48 workers, including 32/37 residents and all workers previously positive at RT-PCR. Follow up serology disclosed antibodies in two additional workers with recent symptoms at the time of screening. The professionals in close contact with residents had more infections (47/226 - 20·79% vs 1/60 - 1.66%; p=0·00013 Fisher exact test). A suspicious clinical score was present in 44/64 residents and in 41/50 workers who tested positive with either method with totally asymptomatic disease more frequent among residents 28.1% vs 10.0% (p = 0.019 Fisher exact test). Integration of RT-PCR testing with clinico-serological screening provided additional information useful to implement protective measures. Rapid serology tests demonstrated efficient and particularly suited for older people less able to move/cooperate.